Public Perspectives Regarding Covid-19 Pandemic: A Survey of Adults in Jakarta Bogor Depok Tangerang Bekasi Area - Desmawati Desmawati; Farahdina Bachtiar (Poltekkes Kemenkes Jakarta III, 2021)
The first Covid-19 case was reported on March 2nd, 2020, in Indonesia. Then, the graphic trend of infected people has risen sharply, particularly in The Jakarta Greater Area: Jakarta, Bogor, Depok, Tangerang, Bekasi (Jabodetabek), as the epicenter. As a quantitative approach, this study aims to investigate people in Jabodetabek about their perspective on the Covid-19 Pandemic. Two hundred ninety-seven residents participated as respondents in fulfilling a self-developed questionnaire spread through online schema. Descriptive analyses were used to explain the data found. The results showed that 65.85 % of the participants have a positive perspective towards characteristics of the Covid-19, 66.13% have a positive perspective toward values, belief, and culture in the environment related to the Covid-19, 71.11% have positive awareness of infectious diseases, and 81.32% have a positive perspective towards services or policies of the government with local wisdom. In conclusion, the public perspective regarding the Covid-19 pandemic in Indonesia, especially people in the Jabodetabek, is good. However, there were still some participants who did not believe in the Covid-19 Pandemic. Increasing people awareness is needed to control Covid-19 transmission in Indonesia. Therefore, it is recommended to increase health promotion activities (rebuild trust, the precautionary principle, social distancing or physical distancing, washing hands and wearing masks), providing psychosocial support (optimism, quick response, and detection, communication with each other).